2022
DOI: 10.3390/ijms231810257
|View full text |Cite
|
Sign up to set email alerts
|

Psychostimulants Modafinil, Atomoxetine and Guanfacine Impair Bone Cell Differentiation and MSC Migration

Abstract: Attention deficit hyperactivity disorder (ADHD) is one of the most common worldwide mental disorders in children, young and adults. If left untreated, the disorder can continue into adulthood. The abuse of ADHD-related drugs to improve mental performance for studying, working and everyday life is also rising. The potentially high number of subjects with controlled or uncontrolled use of such substances increases the impact of possible side effects. It has been shown before that the early ADHD drug methylphenid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Non-stimulants (such as atomoxetine and guanfacine) are the second-line treatment for ADHD; however, these are less effective than stimulants and have a delayed onset of action. It has also been shown that atomoxetine and guanfacine negatively influence mesenchymal stem cell migration during bone formation (Wagener et al, 2022). Therefore, there is a pressing need for new therapeutic agents that act without these side effects (e.g., reduced physical growth) and dependence potential (Sharma et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Non-stimulants (such as atomoxetine and guanfacine) are the second-line treatment for ADHD; however, these are less effective than stimulants and have a delayed onset of action. It has also been shown that atomoxetine and guanfacine negatively influence mesenchymal stem cell migration during bone formation (Wagener et al, 2022). Therefore, there is a pressing need for new therapeutic agents that act without these side effects (e.g., reduced physical growth) and dependence potential (Sharma et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Wagener and colleagues were recently able to show that modafinil, atomoxetine, and guanfacine inhibited hMSC osteogenic differentiation and migration without inducing apoptosis or necrosis. The migration inhibitory effect of these psychostimulants could be abolished by the administration of the selective beta-2 blocker ICI-118551 [ 14 ]. For the first time, this research will investigate the effects of the three psychostimulants on chondrogenic and osteogenic differentiation of three-dimensional hMSC and MG63 cell spheroids.…”
Section: Introductionmentioning
confidence: 99%